A Multidisciplinary Approach to the Management of Atypical Osseous Epithelioid Hemangioendothelioma. (18th February 2014) - Ma, J. K.; Barr, J.; Vijayakumar, S.
Abstract : Hemangioendothelioma is a rare vascular tumor of intermediate malignant potential. Though epithelioid hemangioendothelioma (EH) is commonly found in soft tissues, it has been known to be present in skeletal tissues. The authors present a case of a 50-year-old woman diagnosed with EH of the iliac bone and acetabulum, who experienced pathological fracture at presentation. This report describes a multidisciplinary approach to the management that includes initial incisional biopsy, curettage, and bone grafting, followed by Intensity Modulated Radiation Therapy. The patient finally underwent hemipelvic resection with allograft reconstruction after recurrence. Histopathological study revealed osseous EH of low mitotic activity that stained positively for CD31, CD34, vimentin, and Factor VIII. Herein, the authors discuss the imaging characteristics, histopathological aspects, cytogenetic findings, and the radiobiological behavior of osseous EH. After an aggressive multidisciplinary intervention, the patient is able to achieve local control with no evidence of distal metastatic disease.